Importância da mobilidade espacial para a expansão dos vetores norte-central e sul da Região Metropolitana de Belo Horizonte na virada do século XXI - Fernanda Pereira Mendes Motta (2008)
Population movements have always been of utmost importance to the expansion of large urban centers. In Belo Horizontes Metropolitan Region it was not different. Capitals peripheral cities have expanded and grown through interstate, intrastate and intra-metropolitans migrations, generating a large and continuous daily displacement of population throughout the metropolitan space. That is mainly due to the distance between the housing and work places, forming what we call commuting flow networks. Physical municipal metropolitans limits have lost their importance considering the powerful metropolization process that has taken place over the capital peripheral cities, however, the expansion of metropolis regions has occurred in a differentiated way depending, above it all, of the states investments and real estate markets performance. Two vectors of the metropolitans expansion calls our attention to the form this expansion is happening: the vectors North-Central and South. The North-Central vector was developed as a commuter suburb for the lower income population, as they search for popular land divisions, even the illegal ones, to establish themselves in taking advantage of its lower cost and good accessibility. The South Vector is characterized, in its vast majority, by a high incoming population expansion, as these are looking for a better life quality, usually offered through the closed condominiums that have become dormitory cities for the high income population. The general objective of this work is to identify the population movements that, in the turn for Century XXI, had contributed to the populations growth in the RMBH and to the increase in the commuting mobility as well. Moreover, it was also important to identify mobility distinguishing factors that had contributed to a major differentiation between the North-Central and South vectors. The results had shown that, although we have quantitative differences in populations mobility on those regions, structurally, mobility acts independently from the vector. The land market satisfies demands from the rich ones but from the poor ones as well and these both groups tend to daily commute to the very same regions, carrying through even more population exchanges with the Inter-vectors regions (fields).